Blood ritual in the Hebrew Bible : meaning and power - Gilders, William K., 1967- (Baltimore : The Johns Hopkins University Press, 2004)
"In ancient Israelite sacrifice as represented in the Hebrew Bible, the handling and use of the blood of sacrificed animals took many forms and served different functions. The Hebrew Bible refers to tossing sacrificial blood onto an altar or an assembly of people, daubing it on the altar's horns or parts of the human body, and sprinkling it on or in front of sacred objects." "William K. Gilders investigates the significance of these blood rituals. Offering a close reading of Leviticus 17:11, Gilders emphasizes the secondary and innovative character of this biblical text, which has often been treated as a key for understanding biblical blood ritual. The author also examines evidence from Ezekiel and 2 Chronicles."--BOOK JACKET.
1. The identification of blood with "life" : a conceptual foundation? -- 2. Cultic blood manipulation : an entry to the textual corpus -- 3. The blood of the burnt offering -- 4. Blood manipulation in the sacrifice of well-being, the ordination offering, and the reparation offering -- 5. The Hatta't blood manipulations in P -- 6. Blood manipulation in Ezekiel and 2 Chronicles -- 7. Leviticus 17:11 and the power of blood.
Includes bibliographical references (p. [235]-247) and indexes.
Keywords: Sacrifice -- Judaism; Blood in the Bible; Blood -- Religious aspects -- Judaism